Restoring communal harmony in India : a critical analysis of Wahiduddin Khan’s ideas - Khalil Ahmad,
Since India’s independence and partition from Pakistan, the relationship between Hindus and Muslims has been marked by continuous conflict and mutual distrust. The effects of the British divide and rule strategy that pitted Muslims and Hindus against one another became a hallmark of the relationship between the two communities in the postcolonial period. Such divisions were greatly exacerbated with the coming to power of those who believed in Hindutva or ethnic absolutism. Islamophobia became normalized. Many Muslim scholars have come forward to address this quandary, foremost among which was the late Wahiduddin Khan (1925-2021). This paper investigates Khan’s thoughts about communal harmony in post-independent India. I argue that Khan called for a reformation of Muslim minds, urging them to move beyond an isolationist mentality and find possibilities to develop their society within the status quo. Nevertheless, fraternity, correlation, and communitarianism are to be practiced obtaining religious harmony. Further, Khan’s understanding of the treaty of Ḥudaibiyyah as a panacea to reconcile religious harmony seems insufficient.